Dampak Pandemi Covid-19 Terhadap Penghasilan Buruh Migran Di Desa Payaman Solokuro Lamongan - Agus Wahid Suyoto; Noval Abdillah (BULLET : Jurnal Multidisiplin Ilmu, 2023)
The majority of residents of Payaman Village, Solokuro District, Lamongan Regency choose to work as Indonesian Migrant Workers in Malaysia. The high interest of the people in Payaman Village was supported by the existence of facilities providing services for the Channeling of Indonesian Migrant Workers to Malaysia which are easy to find in Payaman Village, Solokuro District, Lamongan Regency. However, COVID-19 pandemic has caused many migrant workers, mostly Indonesian Migrant Workers choose to come in Indonesia, due to regulations in Malaysia which tighten rules for activities in that country. This situation makes the Indonesian Migrant Workers don’t have other jobs when they come home. This study aims to determine the effect of the impact of the COVID19 pandemic on the income of migrant workers in Payaman village. The variables in this study are the impact of COVID-19 as a free variable and the income of migrant workers as a bound variable. This research uses quantitative methods using primary data in the form of questionnaires and field studies. The population in this study was the payaman village community, with a total sample of 85 people. The data analysis technique used is a simple linear regression analysis and then processed using the SPSS 25.0 program. The result of this study is that the impact of Covid-19 has a significant effect on the income of migrant workers in Payaman Solokuro Lamongan Village. This is indicated by the regression coefficient value of 7,823 t value Calculate the Covid-19 Impact variable is 9,366 while the table t value is 6,354.